A Descriptive Study of the Shifting Television Consumption Behavior of Generation Z in the Digital Era: A Survey of Young Audiences in Bandar Lampung - Agung Wibawa; Hestin Oktiani; Toni Wijaya; Jaya Aji (Penerbit Goodwood, 2026)
Purpose: This study examines the shift in television consumption behavior among Generation Z in the digital era, with a specific focus on young audiences in Bandar Lampung. The rapid advancement of digital technology has influenced patterns of access, viewing duration, and media consumption preferences, leading to a decline in the dominance of conventional television. This study aims to systematically describe the characteristics and patterns of television consumption among Generation Z. Research Methodology: A quantitative descriptive approach was employed using a survey method involving 200 respondents aged 17–23 years, selected through purposive sampling. Data were collected using a structured online questionnaire and analyzed using frequency distribution and percentage techniques. Results: The findings reveal a significant shift from conventional television to digital platforms, as indicated by the dominance of internet-based streaming access (28%). The majority of respondents reported watching television for less than one hour per day (61.5%), primarily during prime time (6:00–9:00 PM). Viewing activities were often accompanied by multitasking behaviors, such as eating or using digital devices. Content preferences were largely dominated by entertainment programs, particularly children’s shows and dramas. These findings indicate that television continues to play a role, but its function has shifted to that of a complementary medium within the digital media ecosystem. Limitations: This study is limited by its use of a descriptive quantitative approach, which focuses on identifying patterns without examining causal relationships between variables Contributions: This study contributes empirically to the field of media communication and offers practical implications for the broadcasting industry to adapt through content innovation and digital distribution strategies. Keywords: Generation Z; Television Consumption; Media Shift; Digital Media; Consumption Behavior.